1995
DOI: 10.22358/jafs/69793/1995
|View full text |Cite
|
Sign up to set email alerts
|

Ileal and faecal digestibility of Jerusalem artichokes (<i>Helianthus tuberosus</i> L.) in pigs

Abstract: Ileal and faecal digestibility of nutrients was studied on 8 intact and 4 ileorectostomized 45 kg pigs assigned at random according to a replicated 2x2 Latin square design to one of two diets containing either refined sucrose or Jerusalem artichoke tubers (fresh, whole) as the only source of energy. The diets were formulated with soyabean meal to be isonitrogenous. Ileal organic mather (OM) digestibility of Jerusalem artichoke diet was significantly lower (P< 0.001) than of the sucrose diet (48.5 vs 89.1%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
3
9
1
Order By: Relevance
“…However, the introduction of Jerusalem artichokes into a sugar cane molasses diet led to a considerable increase in faecal bulk, in agreement with previous observations by Ly et al (1995). In this connection, microbial digestion of fructans rather than that of cell wall or non-starch polysaccharides contained in Jerusalem artichokes could be responsible for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the introduction of Jerusalem artichokes into a sugar cane molasses diet led to a considerable increase in faecal bulk, in agreement with previous observations by Ly et al (1995). In this connection, microbial digestion of fructans rather than that of cell wall or non-starch polysaccharides contained in Jerusalem artichokes could be responsible for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis arises from results of Graham andÁman (1986) who found that precaecal and faecal DM digestibility in Jerusalem artichokes was 40 and 90%, respectively. Comparable values have been obtained for artichoke tubers (Ly et al, 1995). Therefore, fructans from Jerusalem artichokes degraded in the large intestine may largely increase faecal bulk and produce softer faeces, similarly as is the case with soluble dietary fibre in humans (Stephen and Cumming, 1980), rats (Nyman and Asp, 1982) and pigs (Graham and Aman, 1987;.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The most signifficant reduction of enteric bacteria was observed in T3 group piglets, that indicated the synergistic effect of probiotics. Other scientists (Ly et al 1995, Nemcová et al 1999 observed that 3g FOS/day and 2g Lactobacillus paracasei not only significantly reduced Enterobacteriaceae, but also essentially increased total aerobes, anaerobes and lactobacilli. Commonly, reduction of pathogenic microorganisms in gut of animals can be explained by the fact that LAB reduces pH in the luminal contents, which can inhibit the proliferation of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 91%